Accelerated neuroregulation for therapy of opiate dependency (Medical Journal of Indonesia, 2004)
Acute weaning from chronic opioid abuse during general anesthesia is usually followed by adrenergic outflow effects. This article is to report our experience with accelerated neuroregulation that reverses the physical and psychological dependency. After a comprehensive psychological and medical examination, 361 heroin dependent patients were admitted to ICU to be hospitalized for a full 24 or 36 hours, including a 6 hour pre-procedure medication process (solbutamol, clonidine, diazepam, ranitidine, omeprazole, vitamin C, octreotide, and ondansetron). Anesthesia was induced with midazolam and propofol iv and maintained with propofol infusion. Naltrexon, clonidine, octreotide, and diazepam were then administered. Anesthesia was maintained for 3 ½ - 5 hours depending on severity of withdrawal symptoms precipitated by naltrexone. Analgetics and sedatives were given as needed afterwards. Upon discharge on the following day, patient was prescribed a regimen of oral naltrexone for 10-12 months. All 361 patients were successfully detoxified without any adverse anesthetic events. The side effects encountered were fatigue, insomnia, drowsy, shivering, abdominal pain, nausea, diarrhoea, myalgia, goose bumps and uncomfortable feeling. In most of the patients these symptoms disappeared without any treatment. Symptomatic treatments were needed in 32.7% of patients. In all 166 patients who completed their naltrexone maintenance treatment, craving disappeared in the 10th month. The main problem was the low patient compliance to oral naltrexone, so that only 45.9% of the patients completed their therapy. Conclusion: Accelerated neuroregulation which includes naltrexone maintenance treatment (10-12 months) was highly effective to detoxify and to abolish craving in the heroin dependent patients. (Med J Indones 2004; 13: 53-8) Keywords: detoxification, craving management